2019
DOI: 10.1016/j.ijnurstu.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Care staff’s self-efficacy regarding end-of-life communication in the long-term care setting: Results of the PACE cross-sectional study in six European countries

Abstract: Background: An important part of palliative care is discussing preferences at end of life, however such conversations may not often occur. Care staff with greater self-efficacy towards end-of-life communication are probably more likely to have such discussions, however, there is a lack of research on self-efficacy towards end-of-life discussions among long-term care staff in Europe and related factors. Objectives: Firstly, to describe and compare the self-efficacy level of long-term care staff regarding end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 44 publications
3
46
1
1
Order By: Relevance
“…Previous studies have reported that EOL care education programs improve EOL care knowledge among nurses [5,6,42]. Considering knowledge was a significant predictor of self- [7], and 83.8% among Japanese oncology nurses [12]. Nevertheless, the overall positive attitude toward care of dying in our study is somewhat encouraging and may reflect the earlier acceptance of the national palliative care system and education in Mongolia compare to other LMICs [3].…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Previous studies have reported that EOL care education programs improve EOL care knowledge among nurses [5,6,42]. Considering knowledge was a significant predictor of self- [7], and 83.8% among Japanese oncology nurses [12]. Nevertheless, the overall positive attitude toward care of dying in our study is somewhat encouraging and may reflect the earlier acceptance of the national palliative care system and education in Mongolia compare to other LMICs [3].…”
Section: Discussioncontrasting
confidence: 41%
“…The mean FATCOD score as a percentage of the total score in this study was 69.1%, which is lower than 86.0% among oncology nurses in the United States [ 43 ], 79.3% among non-palliative care nurses in Australia [ 7 ], and 83.8% among Japanese oncology nurses [ 12 ]. Nevertheless, the overall positive attitude toward care of dying in our study is somewhat encouraging and may reflect the earlier acceptance of the national palliative care system and education in Mongolia compare to other LMICs [ 3 ].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…W Europie, niestety, pomimo rozwoju wielu różnych specjalizacji w pielęgniarstwie nadal nie ma przepisów, które wzmocniłyby pozycję pielęgniarek w ten sposób [78,79]. Wyniki projektu PACE pokazały również, że poziom wiedzy i umiejętności personelu placówek opiekuńczych z zakresu podstaw opieki paliatywnej jest w wielu krajach niewystarczający i wymaga prowadzenia szkoleń w celu ich poprawy [21,80].…”
Section: Różnice W Jakości Komunikacji Lekarz-rodzina Między Krajami unclassified